Classification of semi‐automated flare readings using the Kowa FM 700 laser cell flare meter in patients with uveitis. (26th September 2015) - Agrawal, Rupesh; Keane, Pearse A.; Singh, Jasmin; Saihan, Zubin; Kontos, Andreas; Pavesio, Carlos E.
Abstract: Purpose: To propose a classification system to grade semi‐automated flare readings and assess its correlation with clinical flare grading and also to explore the utility of an additional step in clinical flare assessment between grades 0 and 1. Methods: Semi‐automated flare readings from 103 eyes with uveitis were taken using the Kowa FM 700 laser flare meter and classified into two models (LFCM and LFCM_1), and introduction of a 0.5 step in flare grading was explored. Results: Good correlation was present between the conventional SUN clinical flare and the proposed clinical classification for flare (weighted kappa (WK) = 89.64%, p < 0.001). Semi‐automated flare grading (LFCM and LFCM_1) had WK agreement of 82.52% and 79.85% (p < 0.001) with conventional SUN clinical flare grading. Conclusions: The proposed classification system for semi‐automated laser flare readings (LFCM) allows stratification of measurements into grades analogous to clinical flare grades and correlates well with conventional clinical flare grading.